THE EFFECT OF DIFFERENT CUTTING TIMES ON FORAGE QUALITY TRAITS OF ALFALFA (Medicago sativa L.) GENOTYPES AND EVALUATIONS WITH BIPLOT ANALYSIS - Sayar, Mehmet Salih; Basbag, Mehmet; Cacan, Erdal; Karan, Halil (Parlar Scientific Publications (P S P), 2022)
This study was conducted to determine the effect of different cutting times on the forage quality traits of twenty-four alfalfa (Medicago sativa L.) genotypes. For this reason, a field trial was established according to separated plots in randomized blocks design with three replications in ecological conditions of Diyarbakir province, Turkey, in 2020. The three plant maturity stages were determined as cutting times. These stages were respectively the pre-flowering, 10% flowering and full flowering periods of alfalfa genotypes. Results of the study revealed that statically highly significant (P<0.01) differences were determined among the cutting times for all of the investigated traits. And the investigated traits had ranges as follow among the cutting times and the alfalfa genotypes; dry matter content (DM) 22.33-31.36%, crude protein content (CP) 14.67-25.87%, acid detergent fiber (ADF) content 25.77-44.10%, neutral detergent fiber (NDF) content 35.40-51.27%, digestible dry matter (DDM) content 54.55-68.85%, dry matter intake (DMI) 2.34-3.40%, metabolizable energy (ME) 8.09-10.84 MJ/kg DM and relative feed value (RFV) 98.98-181.26. Additionally, it was determined that digestibility and consumption status of alfalfa forages decreased with delaying of cutting times. Biplot analysis revealed that when all of the forage quality traits and forage dry matter content were evaluated together, 2nd cutting time, 10% flowering period, was determined as the most appropriate forage harvesting time for alfalfa genotypes. It also showed that there were highly significant (P<0.01) and positive relations among CP, DDM, DMI, ME and RFV traits, and Iside (16), Emiliana (9), Elci (8) and Bilensoy (3) alfalfa cultivars came to fore in terms of the five important forage quality traits.
Keywords: ADF content; alfalfa (Medicago sativa L.); biplot analysis; forage digestibility; NDF content